Применение Ateb-функций для построения решений некоторых нелинейных дифференциальных уравнений в частных производных - Сокил, Б.И. (Український математичний журнал, 1996)
We construct asymptotic approximations of one-frequency solutions of some nonlinear partial differential equations by using periodic Ateb-functions.